Sensitivity of capsular-producing Streptococcus thermophilus strains to bacteriophage adsorption - Rodriguez, Maria Cecilia (2008)
Aims: To determine whether the presence and type of exopolysaccharides (EPS), slime-EPS or capsular, and the structural characteristics of the polymers produced by Streptococcus thermophilus strains could interfere with or be involved in phage adsorption. Methods and Results: Phage-host interactions between eight EPS-producing Strep. thermophilus strains (CRL419, 638, 804, 810, 815, 817, 821, 1190) and five streptococcus specific phages (φYsca, φ3, φ5, φ6, φ8) isolated from Argentinean faulty fermentation failed yoghurts were evaluated. No relationship was found between the EPS chemical composition and the phage sensitivity/resistance phenotype. In general, the capsular-producing strains were more sensitive to phage attacks than the noncapsular-producing strains. Streptococcus thermophilus CRL1190 (capsular-producing) was the only strain sensitive to all bacteriophages and showed the highest efficiency of plating. Phage adsorption to a capsular-negative, EPS low-producing mutant of strain CRL1190 was reduced, especially for φYcsa and φ8. Conclusions: The presence of capsular polysaccharide surrounding the cells of Strep. thermophilus strains could play a role in the adsorption of specific phages to the cells. Significance and Impact of the Study: Capsular-producing Strep. thermophilus strains should be evaluated for their bacteriophage sensitivity if they are included in starter cultures for the fermented food industry.